Eğitilebilir Zihinsel Engelli Çocuklarda Müzik Aletlerinin Görsel Destekli Algılanabilirliği Üzerine Bir Çalışma (İstanbul / Sancaktepe Örneği) - Yılma, Günsu; Uçan, Bahadır (The Turkish Online Journal of Design Art and Communication, 2014)
The purpose of this research is to examine and investigate the perception ability of musical instruments of low mentally retarded children with the support of visual elements. The research is conducted for every children individually in a special education and rehabilitation centre. The problematic of this research is the level of perception ability of musical instruments with visual support on mentally handicapped children. The research is applied with a qualitative approach. Data were obtained with the recorder, then they were turned into texts and analyzed with content analysis method.
Keywords: Zihinsel Engelli Çocuk; Piktogram; Algı; Müzik; Mentally Retarded Children; Pictogram; Perception; Music